2010
DOI: 10.2174/1874943701003010136
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Electromyographic Activation Patterns of Trunk Muscles During Walking

Abstract: Abstract:It is well known that, in spite of its crucial role in the posture, locomotion and voluntary movements, trunk has received less consideration from researchers than upper and lower limbs. On the other hand, rehabilitative interventions of patients with upper motoneuron syndrome have always been focused firstly on treatment and recovery of trunk's posture during standing, sitting and walking.Trunk is a complex anatomical structure and it is composed by a large variety of bones, articulations, ligaments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As the paraspinal muscles function as the antigravity muscles in posture maintenance, these muscles are important for better quality of physical activity. (25, 26) Among the paraspinal muscles, the ESM functions mainly during ambulation, (27) and it has been found to correlate with survival and physiologic function in several diseases. (28,29,30) This study also showed that patients with a low quantity of the ESM and walking disorder had shorter survival than the other group.…”
Section: Discussionmentioning
confidence: 99%
“…As the paraspinal muscles function as the antigravity muscles in posture maintenance, these muscles are important for better quality of physical activity. (25, 26) Among the paraspinal muscles, the ESM functions mainly during ambulation, (27) and it has been found to correlate with survival and physiologic function in several diseases. (28,29,30) This study also showed that patients with a low quantity of the ESM and walking disorder had shorter survival than the other group.…”
Section: Discussionmentioning
confidence: 99%
“…Muscles of the trunk, particularly the abdominal and lumbar multifidus muscles (MF), are postural muscles tonically active during daily upright activities and essential for the stability of the spine, balance, and posture . Trunk muscle size is correlated with strength, and among older adults, trunk muscle strength has been found to be associated with mobility and falls .…”
Section: Introductionmentioning
confidence: 99%
“…Muscles of the trunk, particularly the abdominal and lumbar multifidus muscles (MF), are postural muscles tonically active during daily upright activities 16 and essential for the stability of the spine, balance, and posture. [17][18][19] Trunk muscle size is correlated with strength, 20,21 and among older adults, trunk muscle strength has been found to be associated with mobility and falls. 22,23 The effect of vitamin D supplementation on muscles of the trunk is of particular interest because low 25(OH) D levels are associated with decreased postural balance 13 and increased risk of falls in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Trunk merupakan struktur anatomis yang melibatkan leher, thorax, abdomen dan panggul, ketiga struktur anatomis tersebut terhubung dengan tulang belakang, tulang belakang sendiri mempunyai 4 lengkungan fisiologis yang disebut sebagai kurva natural, yakni segmen sacral dan thorax mempunyai lengkungan cembung kearah belakang, sedangkan segmen cervical dan lumbal mempunyai lengkungan cembung kearah depan (Cioni et al, 2014). Otot trunk utama bagian belakang meliputi splenius capitis, erector spine, transversospinalis, interspinalis, intertransversari, lattisimus dorsi, rhomboid dan levator scapulae, otot tersebut terdiri dari otot superficial dan deep muscle, dilihat dari aspek kinesiologi, otot trunk terbagi menjadi local system dalam perannya melakukan stabilisasi (stability) dan global system dalam perananya melakukan pergerakan (mobility), otot yang termasuk kedalam local system teraktivasi terus menerus meskipun dalam intensitas rendah dan tidak menghasilkan gerakan tubuh, sedangkan otot yang termasuk kedalam global system berkontraksi menghasilkan gerakan tubuh.…”
unclassified